Braxton Bragg and Confederate defeat. - Hallock, Judith Lee, 1940- (University of Alabama Press, 1991)
In the Summer of 1863, Confederate General Braxton Bragg was commander of the Army of Tennessee, still reeling from its defeat in January at Murfreesboro, Tenn.